2017
DOI: 10.1158/0008-5472.can-17-0917
|View full text |Cite
|
Sign up to set email alerts
|

Dual Targeting of Insulin Receptor and KIT in Imatinib-Resistant Gastrointestinal Stromal Tumors

Abstract: Oncogenic KIT or PDGFRA receptor tyrosine kinase (RTK) mutations are compelling therapeutic targets in gastrointestinal stromal tumors (GIST), and treatment with the KIT/PDGFRA inhibitor imatinib is the standard of care for patients with metastatic GIST. Most GISTs eventually acquire imatinib resistance due to secondary mutations in the KIT kinase domain, but it is unclear whether these genomic resistance mechanisms require other cellular adaptations to create a clinically meaningful imatinib-resistant state. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 43 publications
4
17
0
Order By: Relevance
“…41 Linsitinib has been proven to have antiproliferative effects in cell lines and xenograft models in a variety of cancers. 42,43 In our study, we observed that linsitinib treatment blocked the IGF-1-induced deacetylation of ENO2 and suppressed EMT, thereby inhibiting tumor growth and liver metastasis, indicating the potential clinical value of linsitinib in preventing liver metastasis in patients with deacetylated ENO2.…”
Section: Discussionmentioning
confidence: 60%
“…41 Linsitinib has been proven to have antiproliferative effects in cell lines and xenograft models in a variety of cancers. 42,43 In our study, we observed that linsitinib treatment blocked the IGF-1-induced deacetylation of ENO2 and suppressed EMT, thereby inhibiting tumor growth and liver metastasis, indicating the potential clinical value of linsitinib in preventing liver metastasis in patients with deacetylated ENO2.…”
Section: Discussionmentioning
confidence: 60%
“…Colony formation assays were performed as published previously with minor modifications [12]. In brief, GIST48B and PC-9 cells were plated at 5000 and 3,000 cells/well in 6-well plates, respectively, and cultured in RPMI 1640, for 6 days before treatment with gefitinib.…”
Section: Colony Formation Assaymentioning
confidence: 99%
“…Although KIT inhibition by imatinib represents a major therapeutic advance for patients with inoperable GIST, most patients eventually experience clinical progression due to multiple imatinib-resistant mechanisms, which include acquisition of secondary mutations in the KIT kinase domain [11,12], genomic amplification of KIT, and activation of alternate RTKs [2]. Approximately 10% of KIT-positive GISTs lose KIT expression at time of clinical progression during imatinib therapy [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Aberrant signaling pathways are involved in carcinogenic processes, such as RTK and FAK-p53-MDM2 signaling. 52,53 Thus, molecular targeted inhibitors against these aberrant signals also may deliver a new combination strategy with oncolytic virotherapy for future PDAC treatment.…”
Section: Discussionmentioning
confidence: 99%